The neopentencostal political discurs in the presidential elections in Costa Rica: An analysis from the theory of justice of John Rawls - A. Aguilar Ramírez, Esteban (2021)
This article analyzes the speeches and statements made by members of the National Restoration Party, especially its candidate for president, during the 2018 electoral campaign in Costa Rica, on issues related to human rights, such as equal marriage, abortion, the so-called traditional family, among others. Based on this, we decided to analyze whether this type of statements and speeches could be classified as hate speech or calls for intolerance and, therefore, should be limited and not tolerated, or if, on the contrary, said limitation could be understood as a violation of freedom of expression.